AmyloWiki: an integrated database for Bacillus velezensis FZB42, the model strain for plant growth-promoting Bacilli. (19th June 2019) - Fan, Ben; Wang, Cong; Ding, Xiaolei; Zhu, Bingyao; Song, Xiaofeng; Borriss, Rainer
Abstract: Since its isolation 20 years ago, many studies have been devoted to Bacillus velezensis FZB42 (former name Bacillus amyloliquefaciens subsp. plantarum FZB42), which has been gradually accepted as a model organism for Gram-positive rhizobacteria. FZB42 is different from another widely studied bacterial strain, Bacillus subtilis 168, in its many features that are closely associated with plants. FZB42 represents a large group of Bacillus isolates that are beneficial to plants and of great importance in agriculture. In this work a database for FZB42 named 'AmyloWiki' is built to integrate all information of FZB42 available to date. The information includes the genomic, transcriptomic, proteomic, post-translational data as well as FZB42 unique genes, protein regulators, mutant availability, publications and etc. The website is built up with PHP and MySQL with a function of keyword searching, browsing, data-downloading and other functions.